1998
DOI: 10.1042/bj3290449
|View full text |Cite
|
Sign up to set email alerts
|

NADPH oxidase of chondrocytes contains an isoform of the gp91phox subunit

Abstract: Previously it has been reported that chondrocytic cells produce oxygen free radicals and express the cytosolic components of NADPH oxidase. Here we report the expression of large subunit of the flavocytochrome of NADPH oxidase in chondrocytes and, further, show that the cDNA sequence contains three single base pair differences compared with the phagocyte gp91phox gene sequence. These base-pair differences may account for the different activity profiles reported between phagocytic and non-phagocytic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…Several studies have suggested that the nonphagocytic low-output NAD(P)H oxidase, occurring in most cell types, is an isoform of the phagocytic high-output enzyme (23). Differences have been found in the amino acid sequence of gp91phox (24), the polymorphism of the p22phox gene (25), and the involvement of Rac1 or Rac2 in the regulation of the high-and low-output NAD(P)H oxidase (26). These differences may explain how the production of erythropoietin in B cells of chronic granulomatous patients, who suffer from mutations in the phagocytic cytochrome b 558 , can be induced by hypoxia (27).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested that the nonphagocytic low-output NAD(P)H oxidase, occurring in most cell types, is an isoform of the phagocytic high-output enzyme (23). Differences have been found in the amino acid sequence of gp91phox (24), the polymorphism of the p22phox gene (25), and the involvement of Rac1 or Rac2 in the regulation of the high-and low-output NAD(P)H oxidase (26). These differences may explain how the production of erythropoietin in B cells of chronic granulomatous patients, who suffer from mutations in the phagocytic cytochrome b 558 , can be induced by hypoxia (27).…”
Section: Discussionmentioning
confidence: 98%
“…14 Recently, components of phagocyte-type NADH/NADPH oxidases have been found in several nonphagocytic cell types, including fibroblasts, 42,43 VSM cells, 19,24 coronary endothelial cells, 11,12 renal mesangial cells, 44 chemoreceptor cells, 45 microglia, 46 and bone osteoclasts. 47 In these nonphagocytic cells, it is notable that ROS production is generally of relatively low magnitude and slow kinetics compared with the burstlike millimolar production of the activated neutrophil NADPH oxidase. Potential explanations for this difference could include the possibility that oxidase subunit structures (partic- ularly that of gp91-phox) and/or subunit expression level, stoichiometry, and location are different among the enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the system produces nontoxic amounts of H 2 O 2 , consistent with its potential role in signaling by hormones, growth factors, and cytokines. Despite these differences, human fat cell plasma membranes contain a spectrally detectable cytochrome b 558 (4), suggesting that some of the components of human fat cell oxidase may be similar or identical to those of phagocyte oxidase, as has also been proposed for stimulus-sensitive redox activities of other non-phagocytic cells such as endothelia (29), fibroblasts (30,31), mesangial cells (32), chondrocytes (33), vascular smooth muscle cells (34 -36), and adventitial cells (37).…”
Section: G Protein ␤␥-Subunits Mediating the ␤-Adrenergic Inhibition mentioning
confidence: 99%